Extending the Lasing Wavelength Coverage of Organic Semiconductor Nanofibers by Periodic Organic–Organic Heteroepitaxy. Issue 2 (12th February 2013) - Quochi, Francesco; Schwabegger, Günther; Simbrunner, Clemens; Floris, Francesco; Saba, Michele; Mura, Andrea; Sitter, Helmut; Bongiovanni, Giovanni
<x xml:space="preserve">Abstract</x> Organic–organic heteropitaxy based on alternating and periodic deposition of para‐sexiphenyl and alpha‐sexithiophene on muscovite mica enables the fabrication of organic semiconductor nanofibers capable of random lasing with multiband emission and operating in the monomolecular recombination regime at room temperature. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>